Discharge-pulse compression of composite materials - Stanislav V. Neskoromniy; Sergey V. Lemeshev; Stanislav O. Ageyev; Evgeny L Strizhakov (Advanced Engineering Research)
Increasing the operational life of the cutting end of the metalworking tool through face-hardening with powdered materials is an urgent task. The emphasis is on the research results in the field of electric sintering of powder materials in combination with mechanical pressure. The following perspective methods of the powder materials consolidation are described: electropulse compression (EPC), electro-discharge sintering (EDS), and electric pulse sintering (EPS). The devices for dynamic loading of the powder compositions - pneumatic press, magnetic hammer -are analyzed. A compatible scheme of the pulse compression process implementation - sintering with an inductive-dynamic drive which allows synchronizing the thermal and mechanical effects on the powder composition - is submitted. The process parameters dependencies on the time when the duration of the current passage making a thermal impact does not exceed 200 ms are presented. The possibilities of the pulse process are described.